1988
DOI: 10.1097/00006842-198807000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training in healthy type A middle-aged men: effects on behavioral and cardiovascular responses.

Abstract: Thirty-six healthy Type A men (means = 44.4 years) were randomly assigned to either an aerobic exercise training group or a strength and flexibility training group. Subjects completed a comprehensive psychological assessment battery before and after the exercise programs consisting of behavioral, psychometric, and psychophysiological testing. The behavioral assessment consisted of repeated Type A interviews that were videotaped for subsequent component analyses. The psychometric testing included two self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 30 publications
2
47
0
2
Order By: Relevance
“…Among distressed older adults, it is likely that distress would be more likely to moderate the influence of exercise on wound healing. Indeed, prior studies have documented an inverse relationship between stress and physical exercise (19), and an attenuating effect of exercise on stress responses among middle-aged and older adults (20,21). In this nonstressed sample of older adults, neuroendocrine changes were associated with differential rates of wound healing.…”
Section: Discussionmentioning
confidence: 73%
“…Among distressed older adults, it is likely that distress would be more likely to moderate the influence of exercise on wound healing. Indeed, prior studies have documented an inverse relationship between stress and physical exercise (19), and an attenuating effect of exercise on stress responses among middle-aged and older adults (20,21). In this nonstressed sample of older adults, neuroendocrine changes were associated with differential rates of wound healing.…”
Section: Discussionmentioning
confidence: 73%
“…It may be, for instance, that social or physical activities contribute to the recovery process through a cognitive process of distraction that enables people to detach from their work psychologically (68,69). Moreover, there are indications that people who are more physically fit show more rapid cardiovascular recovery from stressors (84,85), suggesting a physiological mechanism underlying the recovering effect of exercise. Hansen et al (86) provided evidence for a psychological effect of sports activities on well-being by showing that sport rapidly enhanced a person's mood.…”
Section: How Do Personality Characteristics Affect the Recovery Process?mentioning
confidence: 99%
“…4 -5 Hyperresponsiveness of the sympathetic nervous system to psychophysiological stressors is an established model for studying the etiology of coronary heart disease, atherosclerosis, and primary hypertension. 6 -13 Some investigators 14 " 16 have reported that cardiorespiratory fitness is associated with lower sympathetic responsiveness to various stressors (see Crews and Landers 17 for a review), while others 1823 have found no effect (see Peronnet and Szabo 24 for a review). The controversy in this area can be explained partly by a lack of standardization in the measurement of fitness, physical activity, sympathetic activity, and stressor tasks.…”
Section: Effects Of Physical Activity and Fitnessmentioning
confidence: 99%